Structural Properties, Lattice Strain and Transformation of Anatase-Type TiO2 Nanocrystals to Rutile in TiO2-SiO2 Composite - Riazian, Mehran; Daliri Rad, Shima; Montazeri, Naser; Pourshamsian, Khalil (Asian Journal of Chemistry, 2012)
We report the synthesis of TiO2 nanoparticles in anatase and rutile structures in SiO2-TiO2 composite. The SiO2-TiO2 nanostructure was synthesized based on the sol-gel method. The nanoparticles were characterized by X-ray fluorescents, X-ray diffraction, field emission scanning electron microscopy and Fourier transmission infrared absorption (FTIR) techniques. Phase formation was achieved by hydrothermal treatment at elevated temperatures. The anatase nanoparticles were obtained under 300 ºC calcined temperature, while rutile phase were obtained in higher than 300 ºC calcined temperature. The mass fraction of anatase and rutile phases was calculated. It can be fined that as the calcined temperature increases the per cent of rutile phase content grows, as well as when the content of TiO2 in SiO2-TiO2 composite increases, the per cent of rutile phase content grows. The effects of chemical compositions and calcinations temperature on the surface topography and the crystallization of phases were studied.